ISLAMISASI ILMU PENGETAHUAN - Salafudin _ (Jurnal Forum Tarbiyah, 2013)
Advance of science and technology provides convenience on one hand, brings about negative implications for the emergence of the global crisis on the other hand. Science and technology on the one hand gives happiness but on the other hand contribute to the emergence of the global and multidimensional crisis. Therefore, it brings about awareness among some Muslims to perform the reconstruction of science through large projects of Islamization of science. This idea have ups and downs and invite pro and contra in academic circles. The idea of Islamization of knowledge is essentially an idea to find a new modern science but religious and monotheism. This idea is very popular since the beginning of its declaration and until now still being discussed among Muslims, whether they support or reject it. This idea is also very urgent in view of the increasing of intellectual’s awareness to transcend science. This paper is aimed to study the Islamization of knowledge from the background of the Islamization of science, history of the Islamization of science, implementation Islamization of science, and the challenges Islamization of sciences aspect.